Short-term Outcomes of Feminizing Genitoplasty in Childrenwith Congenital Adrenal Hyperplasia: A Five-year Prospective observational study (Journal of Paediatric Surgeons of Bangladesh, 2026)
Aims/ objectives: To find out the beneficial outcomes of early feminizing surgery in patients with DSD due to CAH with virilization. By assessing pre & post operative anatomy, cosmesis & parental satisfaction.Methods: This prospective observational study included 25 patients (aged 2year-11 years) of CAH with virilization who were clinically optimized pre-operatively. Feminizing genitoplasty of these patients were carried out in various Department of Paediatric Surgery in three centers. The study is being conducted with the intention of observing the short-term outcome. Patients were selected by purposive sampling from January 2021 to October 2025, over a period of 5 years.Results: The mean age of the study subject was 6.29±2.3 years. The mean value of cosmetic outcome score was 8.4 on a 10-point scoring system. According to the outcome evaluation: 3 patients (12%) had excellent results, 7 patients (28%) had very good results, 11 patients (44%) had good results, and 4 patients (16%) had fair results. Postoperatively, among the 25 patients: 18 patients (72%) achieved Prader score 0, 11 patients (44%) had clitoral index >1, and 14 patients (56%) had clitoral index